POTENSI LOKAL PULAU TANAKEKE SEBAGAI SUMBER BELAJAR RUMPUN ILMU PENGETAHUAN SOSIAL DI SMA NEGERI 12 TAKALAR - Anshar, Resky Anitha Putri; Padli, Feri; Shasliani, Shasliani (UNM Geographic Journal, 2025)
This study aims to: 1) determine the local potential of Tanakeke Island in Takalar Regency, 2) analyze the local potential of Tanakeke Island so that it can be used as a source of social studies learning to improve learning of social science clusters at SMA Negeri 12 Takalar, and 3) determine the challenges faced in utilizing the local potential of Tanakeke Island as a source of learning. This type of research is qualitative research and descriptive approach.The number of informants in this study was 4 teachers who were determined through purposive sampling techniques with teacher criteria, namely: 1) having a minimum of 5 years of teaching experience at SMA Negeri 12 Takalar, 2) having an educational background relevant to the social sciences, and 3) having knowledge and insight into the culture, history, and economic potential of Tanakeke Island. Data collection techniques were observation, interviews and documentation. Data validity checking was carried out using source triangulation techniques. Data analysis was data reduction, data presentation, and drawing conclusions.The results of the study indicate that: 1) Tanakeke Island has integrated cultural, economic, historical, and social richness. Local wisdom strengthens togetherness and environmental preservation, while the marine resource-based economy still faces challenges in terms of income and access to technology. Family ties and mutual cooperation are the pillars of the community, with community leaders playing an important role in decision-making; 2) The Maudu' Lompoa, Bangko Tappampang, and Pasir Putih Tourism traditions have high educational value for SMA Negeri 12 Takalar in the Social Sciences cluster. These traditions teach cultural preservation, sustainable use of natural resources, and analysis of the economic impact and coastal ecosystems; and 3) Utilization of the local potential of Tanakeke Island as a learning resource for economics, geography, sociology, and history subjects faces obstacles such as limited access to transportation, teaching materials that are less focused on the local context, and minimal teacher training related to local resources.